Pemberontakan Satsuma dan Puisi “Battotai” Karya Toyama Masakazu - Anggia Ariska (Linguistika Kultura)
The Satsuma Rebellion is one of many historical events that have occurred in Japan. Japan is a country that has a very long history, known as a country that has gone through various ages, one of which is the Meiji era or known as the Meiji Restoration. In a work of poetry “Battotai” by Toyama Masakazu can be seen a battle called the “Satsuma rebellion.” In a poem that describes the brave troops of the government army against the enemy using the sword in the Meiji period/Meiji Restoration. The purpose of this writing is to find out and explore the history of Japan through a work of poetry “Battotai.” To reveal the history in the poem used descriptive qualitative research methods. The results of this study find that in the poem "Battotai" the brave troops of the government army against the enemy using swords during the Meiji/Meiji Restoration period were the battle in the Satsuma rebellion. Soldiers of government forces used samurai symbols such as swords. The sword is a symbol of the status of the samurai and courage is a symbol of the ethics/moral principles of the samurai as the code of ethics of the Japanese samurai called Bushido.